2007
DOI: 10.1590/s1413-86702007000200028
|View full text |Cite
|
Sign up to set email alerts
|

Septicemia caused by Vibrio cholerae O1 biotype El Tor, in São Paulo, Brazil

Abstract: We reported a case of septicemia by Vibrio cholerae O1, in São Paulo, Brazil. A 70-year-old male patient, living in an urban area, entered the emergency service having sepsis, dying 12 hours later. Blood culture was positive for Vibrio cholerae O1. This is the first case of bacteremia by Vibrio cholerae O1 reported in South America.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…In 2009, Amin and colleagues reported the difference in invasion pattern of O1 and O139 Vibrio cholerae in rabbit ileum which stated the level of invasion of Vibrio choleraee O139 was more thanO1 El Tor and the pattern of invasion was different [6,[70][71][72][73][74][75][76][77][78]. In this paper we also found that the O139 invaded in a diffuse pattern along with the focal pattern ( Figure 3).…”
Section: Discussionsupporting
confidence: 56%
“…In 2009, Amin and colleagues reported the difference in invasion pattern of O1 and O139 Vibrio cholerae in rabbit ileum which stated the level of invasion of Vibrio choleraee O139 was more thanO1 El Tor and the pattern of invasion was different [6,[70][71][72][73][74][75][76][77][78]. In this paper we also found that the O139 invaded in a diffuse pattern along with the focal pattern ( Figure 3).…”
Section: Discussionsupporting
confidence: 56%
“…Immunocompromised status and prematurity have also been addressed as risk factors. [4][5][6][7][8][9][10] In our case, the patient had leukemia, chemotherapy, damaged mucosal barriers and associated infection with E. coli as predisposing factors. The patient did not have any history of travel or any episode of diarrhea prior to current admission.…”
Section: Discussionmentioning
confidence: 66%
“…The limited reported cases of invasive disease caused by V. cholerae O1 are summarized in Table 1. [4][5][6][7][8][9][10] Pathogenic mechanisms causing invasion in V. cholerae infections are not well recognized. Possible reasons could be pre-existing disruption of mucosal barrier, achlorhydria, simultaneous infection with an invasive pathogen, translocation of viable V. cholerae via M cells and hemolysin production.…”
Section: Discussionmentioning
confidence: 99%